Interactions among insulin resistance, inflammation factors, obesity-related gene polymorphisms, environmental risk factors, and diet in the development of gestational diabetes mellitus. (17th January 2019) - Feng, Yang; Jiang, Chen-Dong; Chang, Ai-Min; Shi, Ying; Gao, Junjun; Zhu, Linlin; Zhang, Zhan
Abstract: Purpose: The aim of this study was to investigate the correlations and interactions between the polymorphisms of insulin resistance-related genes ( ADIPOQ rs2241766), inflammation factors ( TNF-α rs1800629, IL-6 rs1800795), obesity-related genes (GNB3 rs5443, ADRB rs1042714), and risk factors for gestational diabetes mellitus (GDM) such as diet structure in the development of GDM. Materials and methods: This research was conducted among women who visited the third-affiliate hospital of Zhengzhou University for pregnancy checkups from 1 June 2014 to 30 December 2014. Based on the results of a 75-g glucose tolerance test (OGTT), 140 pregnant women with GDM were randomly selected as a part of the GDM group and140 healthy, pregnant women as part of the control group. Relevant clinical and laboratory data for the child and the mother including her pregnancy outcomes and the delivery mode were collected for the epidemiological survey. Results: The results showed that risk factors for GDM are advanced age, the hepatitis B virus, family history of diabetes, high body mass index before pregnancy, and weight gain of ≥10 kg before 24-week gestation. We found that diet structures were severely unbalanced. The polymorphisms rs2241766 and rs5443 were found to potentially be associated with GDM; moreover, a positive interaction was demonstrated between rs2241766 and age, and a negative interaction was demonstrated with weight gain of ≥10 kg before 24-week gestation. Conclusion: Our findings demonstrate that both environmental risk factors and genetic background contribute to the development of GDM.